G2019s LRRK2 promotes mitochondrial fission and increases TNFα-mediated neuroinflammation responses. Issue 2 (4th March 2019) - Ho, Dong Hwan; Lee, Heajin; Son, Ilhong; Seol, Wongi
ABSTRACT: Leucine rich-repeat kinase 2 (LRRK2) is involved in the pathogenesis of Parkinson's disease (PD). LRRK2 has kinase and GTPase activities, and mediates several cell functions, including vesicle trafficking, apoptosis, autophagy, mitochondrial dynamics, and neuroinflammation. G2019S (GS) is the most prevalent mutation of LRRK2. The mutation increases kinase activity, suggesting that this activity is crucial for PD pathogenesis. The activation and inhibition of LRRK2 kinase increases and reduces the levels of proinflammatory cytokines, respectively suggesting that the role of LRRK2 in neuroinflammation is critical for the pathology of PD. Previously, we demonstrated that microglial activation by lipopolysaccharide (LPS) increases mitochondrial fission via the activation of LRRK2 kinase, while LRRK2 kinase inhibition diminishes the fission morphology and release of tumor necrosis factor-alpha (TNFα) in BV2 or rat primary microglia and the brains of GS transgenic mice. In this study, the ectopic expression of GS LRRK2 in BV2 cells significantly elevated the expression of Drp1 along the fragmented mitochondria and decreased mitochondria size compared with controls. GS LRRK2-transfected BV2 cells displayed significantly increased TNFα release and neuronal death. Inhibition of LRRK2 kinase alleviated these features. TNFα levels in brains of GS mice were significantly increased compared to those in their littermates. These data further support our previous findings concerning LPS-induced neuroinflammation and mitochondrial fission in microglia via LRRK2 kinase activation.